2019
DOI: 10.3390/cancers11040525
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Mucolipin-1 Channels in Glioblastoma: Role in Patient’s Survival

Abstract: A link between mucolipin channels and tumors has been recently suggested. Herein, we aim to investigate the transient receptor potential mucolipin (TRPML)-1 relevance in glioblastoma. The expression of this channel was evaluated via qRT-PCR and immunohistochemistry in biopsies from 66 glioblastoma patients and two human glioblastoma cell lines and compared to normal human brain, astrocytes, and epileptic tissues. The subcellular distribution of TRPML-1 was examined via confocal microscopy in the glioma cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 45 publications
(64 reference statements)
3
49
0
Order By: Relevance
“…It is known that Ac deficiency may increase substrate lysosomal CER and even upstream sphingomyelin, but reduces lysosomal Sph or its metabolite, S1P. Some of them were recently shown to alter lysosomal TRPML1 channel activity 71 and Ca 2+ release regulating lysosome trafficking 33,72,73 . The present study tested the hypothesis that the role of Ac may be associated with lysosomal TRPML1-mediated Ca 2+ release.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Ac deficiency may increase substrate lysosomal CER and even upstream sphingomyelin, but reduces lysosomal Sph or its metabolite, S1P. Some of them were recently shown to alter lysosomal TRPML1 channel activity 71 and Ca 2+ release regulating lysosome trafficking 33,72,73 . The present study tested the hypothesis that the role of Ac may be associated with lysosomal TRPML1-mediated Ca 2+ release.…”
Section: Discussionmentioning
confidence: 99%
“…28 For example, the markedly enriched GO terms (MF) in recurrent GBMs were protein heterodimerization activity and structural constituent of ribosome in CGGA database and channel activity and passive transmembrane transporter activity in the TCGA database, although these GO terms have been reported to contribute to GBM progression. [28][29][30][31] Glioma stem cells play critical roles in glioblastoma multiforme chemotherapy resistance and recurrence, such as CD133 cells. 32 Glioma stem cells can self-renew and differentiate into other specific GBM subpopulations, which is involved in activation of Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Besides LSDs, emerging evidence suggests that TRPML1 is also important for cancer cell survival [59][60][61]. Interestingly, the effect of TRPML1 activity modulation on cancer cell survival differs, possibly dependent on the type of cancers and stimuli.…”
Section: Redox-sensing Lysosomal Ion Channels and Diseasesmentioning
confidence: 99%
“…Specifically, TRPML1 inhibition suppresses the growth of triple-negative breast cancers (TNBCs) [59] and reduces the proliferation of oncogenic HRAS-expressing cancer cells [61]. On the other hand, a very recent research reported that glioblastoma (GBM) patients survival are negatively correlated with TRPML1 expression level, while glioma cells are vulnerable to ROS when TRPML1 is activated [60].…”
Section: Redox-sensing Lysosomal Ion Channels and Diseasesmentioning
confidence: 99%